Penguatan Edukasi dan Literasi Anti Korupsi dalam Perspektif Hukum melalui Kegiatan Webinar Pengabdian kepada Masyarakat: Pengabdian - Djuhrijjani Djuhrijjani; Nizla Rohaya; Tiwuk Herawati; Iin Inayah; Ahmad Ahmad; Franky Ariyadi; Eko Sudarmanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Corruption is categorized as an extraordinary crime as it generates extensive and systemic impacts on legal stability, social order, and national development. Therefore, corruption prevention strategies cannot rely solely on repressive measures through law enforcement, but must be supported by the strengthening of legal education and public legal literacy. This Community Service Program (PkM) aims to enhance public understanding and legal awareness of anti-corruption values through the implementation of an educational webinar. The method employed an educative–participatory approach utilizing online media, delivering materials on the legal basis of corruption offenses, principles of integrity, and the active role of society in corruption prevention efforts. The implementation of the program indicated an improvement in participants’ understanding of the concepts and forms of corruption, the governing legal regulations, and the urgency of internalizing a culture of integrity in everyday life. These findings emphasize that webinars serve as an effective, flexible, and adaptive medium for sustainably expanding the reach of anti-corruption legal literacy within the community.